Internal Marketing and Digital Employee Experience in Reducing Nurse Burnout: A Systematic Literature Review - Sharon Dewi Wardoyo; Grace Fresania Kaparang; Shapely Ambalao (Jurnal Economic Resource, 2026)
Nurse burnout remains a critical issue in healthcare systems worldwide, particularly after the COVID-19 pandemic. Previous studies shows that burnout negatively affects nurses’ psychological well-being, organizational commitment, patient safety, and healthcare quality. Simultaneously, healthcare organizations are increasingly implementing internal marketing and digital workplace systems to improve employee experience and organizational performance. However, the integration of internal marketing and digital employee experience in reducing nurse burnout has not been comprehensively synthesized. Objective: This study aimed to systematically review evidence regarding the influence of internal marketing and digital employee experience on reducing nurse burnout. Methods: This review followed the PRISMA 2020 guideline developed by Matthew J. Page and colleagues. Literature searches were conducted using PubMed, Scopus, and Google Scholar databases from 2015–2026. Search terms included “internal marketing,” “digital employee experience,” “nurse burnout,” “organizational commitment,” and “nursing informatics.” Inclusion criteria included English-language studies involving nurses and organizational interventions related to internal marketing or digital workplace experience. Results: 27 articles were eligible and examined, and three main themes such as internal marketing, digital employee experience and major outcomes were identified. Internal marketing strategies such as leadership support, communication, empowerment, reward systems, and organizational culture consistently reduced burnout and improved organizational commitment among nurses. Digital employee experience, including digital communication systems and nursing informatics competency, positively influenced engagement and work satisfaction. However, excessive digital workload and technostress contributed to emotional exhaustion and burnout. Conclusion: Internal marketing and supportive digital employee experience are effective organizational approaches to reducing nurse burnout. Healthcare institutions should integrate employee-centered management and digital transformation strategies to improve nurse well-being and healthcare sustainability.